Adverse Pregnancy Outcomes among Women with Prior Spontaneous or Induced Abortions - Makhlouf, Michel A.; Clifton, Rebecca G.; Roberts, James M.; Myatt, Leslie; Hauth, John C.; Leveno, Kenneth J.; Varner, Michael W.; Thorp, John M., Jr.; Mercer, Brian M.; Peaceman, Alan M.; Ramin, Susan M.; Iams, Jay D.; Sciscione, Anthony; Tolosa, Jorge E.; Sorokin, Yoram; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2014)
Objective The aim of the article is to determine whether prior spontaneous abortion (SAB) or induced abortion (IAB), or the interpregnancy interval are associated with subsequent adverse pregnancy outcomes in nulliparous women.Methods We performed a secondary analysis of data collected from nulliparous women enrolled in a completed trial of vitamins C and E or placebo for preeclampsia prevention. Adjusted odds ratios (ORs) for maternal and fetal outcomes were determined for nulliparous women with prior SABs and IABs as compared with primigravid participants.Results Compared with primigravidas, women with one prior SAB were at increased risk for perinatal death (adj. OR, 1.5; 95% CI, 1.1–2.3) in subsequent pregnancies. Two or more SABs were associated with an increased risk for spontaneous preterm birth (PTB) (adj. OR, 2.6, 95% CI, 1.7–4.0), preterm premature rupture of membranes (PROM) (adj. OR, 2.9; 95% CI, 1.6–5.3), and perinatal death (adj. OR, 2.8; 95% CI, 1.5–5.3). Women with one previous IAB had higher rates of spontaneous PTB (adj. OR, 1.4; 95% CI, 1.0–1.9) and preterm PROM (OR, 2.0; 95% CI, 1.4–3.0). An interpregnancy interval less than 6 months after SAB was not associated with adverse outcomes.Conclusion Nulliparous women with a history of SAB or IAB, especially multiple SABs, are at increased risk for adverse pregnancy outcomes.
Keywords: spontaneous abortion; induced abortion; maternal outcomes; neonatal outcomes